External iliac pseudoaneurysm secondary to medial wall penetration of an acetabular screw: a rare cause of total hip arthroplasty failure 15 years after implantation - Wilson, Jacob M. (Arthroplast Today, 2019)
Vascular injury as a result of total hip arthroplasty (THA) represents an uncommon complication. Although these injuries typically present acutely, delayed presentation has been reported. In this case, a 70-year-old female presented with groin pain and medial thigh numbness 15 years after a left THA. After initially being misdiagnosed, repeat imaging revealed a large external iliac pseudoaneurysm as a result of a transacetabular screw penetrating the medial acetabular wall. The patient underwent staged endovascular exclusion of the pseudoaneurysm, percutaneous drainage, and revision THA. She had resolution of her symptoms. To our knowledge, this is the only reported case of a late vascular injury related to an aseptic THA with well-fixed components. Staged treatment with endovascular exclusion and revision THA is a viable approach.